PATTERN AND DETERMINANT OF SUCCESSFUL SCHOOL TO WORK TRANSITION OF YOUNG PEOPLE IN ISLAMIC DEVELOPING COUNTRIES: EVIDENCE FROM EGYPT, JORDAN AND BANGLADESH - Absor, Muh Ulil; Utomo, Iwu (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
This study considers the impact of conservative cultures, by comparing the patterns and determinants of the successful school-to-work transition of young people in Egypt, Jordan and Bangladesh. This study argues that the most consistent and significant influence of successful transition among male and female youth are micro predictors compared to mezzo and macro predictors. This study found that male and female youth are treated differently during their school-to-work transition. Conservative culture has negative influences on the successful transition of female youth while a positive transition is experienced by male youth. Education is a key strategy in reducing the negative impacts of conservative culture and promoting successful school-to-work transition particularly if both male and female youth are to attain stable employment.